Pengaruh Fintech Peer To Peer Lending Dan Pembayaran Digital Uang Elektronik Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2018-2023 - Putri Septia Ningsih (Jurnal Prospek: Pendidikan Ilmu Sosial dan Ekonomi, 2025)
hand, technological developments have given rise to new innovations such as peer to peer lending and digital payments. These two types of fintech are currently popular financial services. With these two types, it really helps the community because using technology all transaction activities can be carried out. This research aims to determine the influence of fintech peer to peer lending and digital electronic money payments simultaneously on economic growth in Indonesia and to determine the influence of fintech peer to peer lending and digital electronic money payments partially on economic growth in Indonesia. The data used in this research is secondary data from 2018-2023. The analysis used is multiple linear regression analysis. The analytical tool used to carry out the analysis is STATA 17. The results of the research show that the fintech peer to peer lending variable has a positive and significant effect on economic growth in Indonesia, the electronic money digital payment variable has no effect and is not significant on Economic Growth in Indonesia, and simultaneously The fintech variables peer to peer lending and digital electronic money payments influence economic growth in Indonesia.